Advances in electric power and energy : static state estimation - El-Hawary, M. E. (John Wiley & Sons, Inc., 2021)
"A static state estimator (SSE) is a collection of digital computer programs which convert telemetered data into a reliable estimate of the transmission network structure and state by accounting for small random metering-communication errors; uncertainties in system parameter values; bad data due to transients and meter-communication failures; and errors in the network structure due to faulty switch-circuit breaker status information. Failure of SSE at System Operators' facilities has been cited as one of the primary causes for some major blackouts over the two decades"- Resumé vydavatele
Keywords: elektrizační soustavy; matematická optimalizace; electric power systems; mathematical optimization; elektronické knihy; kolektivní monografie; electronic books; collective monographs